Editorial - J. G. Arapura (Journal of Dharma, 1995)
Historically, different religions occupying the same geographical 8S well as cultural space, or existing in just contiguous geographical areas, putting pressures upon the cultures, have had occasions of encounter with one another concerning several things which define a world religion, including the perception of the right way for human beings to live in the world and belief as to what is the true path to salvation, in principle binding for all. Considering human nature, some of these encounters have led not just to disagreements but to clashes, especially when one of the religions in that situation had a historical, genetical connection with another that may be considered the parent religion. The problem could be just as bad or even worse, if one of the religions in question has been considered an alien introduction, and worse still if it bears a salvational message, accompanied by an obligation either divinely mandated or mandated by the sheer force of truth, or so believed, to spread it globally.